Signed Product Cordial and Even Sum Cordial Labeling for the Extended Duplicate Graph of Splitting Graph of Path - R. Avudainayaki; B. Selvam; P. P. Ulaganathan (International Journal of Mathematics And its Applications, 2017)
In this paper, we prove that the extended duplicate graph of splitting graph of path admits signed product cordial, total signed product cordial and even sum cordial labeling.